Предмет: Алгебра,
автор: NiKaEmpty
СРОЧНО Упростите выражение и найдите его значение при х= -0,1
(x-3)2 степерь - (x+3) (x-3)
Ответы
Автор ответа:
0
(x-3)² - (x-3)(x+3) = (x-3)·((x-3)-(x+3)) = -6(x-3) = 18 - 6x
x=0.1, 18 - 6x = 18 - 6·0.1=18-0.6=17.4
Ответ: 17.4
x=0.1, 18 - 6x = 18 - 6·0.1=18-0.6=17.4
Ответ: 17.4
Похожие вопросы
Предмет: Математика,
автор: rinatylianuar
Предмет: Математика,
автор: maria310511
Предмет: Информатика,
автор: Oceanofsadness08
Предмет: Геометрия,
автор: gazizova8456
Предмет: Математика,
автор: lilushks200804